How Might Shadow Price Restrictions Reduce Technical Efficiency? Evidence from a Restricted DEA Analysis of Coffee Farms in Vietnam - Garcia, Andres F. (2012)
We use data from smallholder coffee farms in Vietnam to measure the technical efficiency of coffee producers, and the degree to which potential restrictions on the shadow prices of chemical inputs might reduce overall efficiency among these farmers. Using input-oriented data envelopment analysis (DEA) we find the use of pesticide and herbicide accounts for a relatively small proportion of overall technical efficiency in the sample. We place restrictions on input shadow prices and show that restricting their importance does not dramatically alter patterns or measures of short-run efficiency.